SISTEM PENDUKUNG KEPUTUSAN PENENTUAN PENERIMA BEASISWA BAZNAS KABUPATEN ASAHAN DENGAN METODE SAW - Puspita Deri Syahfitri; Herman Saputra; Wan Mariatul Kifti (JUTSI: Jurnal Teknologi dan Sistem Informasi, 2023)
AAbstract: BAZNAS Regency is a place for collecting and collecting zakat. The zakat distribution program at the Asahan Regency BAZNAS office is engaged in the fields of education, health, da'wah, economy and humanity. In the education program, zakat is distributed for scholarship programs starting from elementary, junior high, high school, undergraduate, masters, and there is also assistance with thesis costs. The problem that occurred in this study was based on data obtained from the BAZNAS Office of Asahan Regency, there was no decision support system in the process of receiving zakat for scholarships, resulting in an error in the scholarship selection process which was not effective and efficient. The purpose of this study is to apply the Simple Additive Weighting (SAW) method in selecting scholarship recipients at the Asahan District BAZNAS Office so that it can assist the Asahan District BAZNAS in the scholarship selection process based on existing criteria. The result of this study is the process of calculating alternative preferences using the Simple Additive Weighting method, student V6 = Rahmawati Saragih as a student who ranks first out of 9 (nine) students registered as scholarship candidates. Keywords: Scholarship; Simple Additive Weighting; Zakat.  Abstrak: BAZNAS Kabupaten merupakan tempat pengumpulan dan penghimpunan zakat. Program penyaluran zakat di kantor BAZNAS Kabupaten Asahan bergerak pada bidang pendidikan, kesehatan, dakwah, ekonomi dan kemanusiaan. Pada program pendidikan, zakat disalurkan untuk program beasiswa mulai dari SD, SMP, SMA, sarjana, magister, dan ada juga bantuan biaya skripsi. Adapun masalah yang terjadi pada penelitian ini berdasarkan data yang diperoleh dari Kantor BAZNAS Kabupaten Asahan belum adanya sistem pendukung keputusan dalam proses penerimaan zakat untuk beasiswa, sehingga terjadi kesalahan dalam proses pemilihan beasiswa yang tidak efektif dan efisien. Adapun Tujuan pada penelitian ini adalah menerapkan metode Simple Additive Weighting (SAW) dalam melakukan pemilihan penerimaan beasiswa pada Kantor BAZNAS Kabupaten Asahan sehingga dapat membantu pihak BAZNAS Kabupaten Asahan dalam proses pemilihan beaiswa berdasarkan kriteria-kriteria yang ada. Hasil dari penelitian ini adalah proses penghitungan preferensi alternatif dengan menggunakan metode Simple Additive Weighting, mahasiswa V6 = Rahmawati Saragih sebagai mahasiswa yang menempati urutan pertama dari 9 (sembilan) mahasiswa yang terdaftar sebagai calon beasiswa. Kata Kunci: Beasiswa; Simple Additive Weighting; Zakat